Interesting Ag3PO4 concave rhombic dodecahedra: the same face with different morphologies and photocatalytic properties. Issue 39 (3rd May 2017) - Guo, Ruirui; Fan, Yaoting; Tang, Yu
Abstract : Different morphologies of Ag3 PO4 with the same crystal face give distinct photocatalytic properties. Abstract : Herein, a novel and interesting Ag3 PO4 crystal with concave rhombic dodecahedra morphology (Ag3 PO4 CRD) via facile wet chemical method is presented. Compared to Ag3 PO4 with rhombic dodecahedra structure (Ag3 PO4 RD), the Ag3 PO4 CRD was also enclosed by 110 facets but with different geometrical shapes, formed through carving out four parallelepipeds at special junctions. The photocatalytic activity of Ag3 PO4 CRD dramatically decreased, this was attributed to the concave nature inducing easier recombination of photogenerated holes and electrons and the reaction with organic molecules being more difficult due to space limitation and the shadow effect. The results indicated that the geometrical distribution of crystal facets could play an important role in determining photocatalytic properties.